2019
DOI: 10.1504/ijmbs.2019.105809
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of border crossing: gender, mobility and border control

Abstract: In recent years, new migration patterns emerged in Europe and border control operations became more complex and broader, resulting in an increasing number of non-nationals detained for migration-related reasons. This paper aims to explore how gender, migration and border control intersect in the lives of women detained for not having authorisation to remain in Portugal. Several visits were made to a detention facility, where ten women detainees were interviewed. Our findings reveal how gender plays a crucial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…11 The interviews were digitally recorded and transcribed verbatim, except in the case of one participant who did not agree to audio record and so her interview was handwritten. All transcripts were subsequently analysed through a thematic narrative analysis (Lykes and Hershberg 2015;Riessman 2008), whose results are reported here and in a previous article about migration pathways, life in Portugal and expectations for the future (Matos and Esposito 2019).…”
Section: A Note On Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…11 The interviews were digitally recorded and transcribed verbatim, except in the case of one participant who did not agree to audio record and so her interview was handwritten. All transcripts were subsequently analysed through a thematic narrative analysis (Lykes and Hershberg 2015;Riessman 2008), whose results are reported here and in a previous article about migration pathways, life in Portugal and expectations for the future (Matos and Esposito 2019).…”
Section: A Note On Methodologymentioning
confidence: 99%
“…Based on evidence provided by this study, Matos and Esposito (2019) started to analyse the trajectories of women confined in Portugal for migration-related reasons. This preliminary work-which focused on women's pathways to illegalisation and detention, as well as on their expectations for the future-found that gender plays a crucial role in their experiences of mobility and crossing borders.…”
Section: Introductionmentioning
confidence: 99%